Profil Status Gizi Remaja SMP YPPK Santu Paulus Abepura - Sarni Rante Allo Bela; Genoveva Chatleen C. Mollet; Nova F. Rumaropen; Rosmin M. Tingginehe; Annisaa Maharani Halim; Maxsi Irmanto (I-Com: Indonesian Community Journal, 2024)
Humans play a crucial role as the primary resource in national development endeavors. Presently, Indonesia's demographic makeup is characterized by a predominant population within the productive age range (15-65 years), encompassing adolescents. The adolescent phase signifies a transition from childhood to adulthood, with nutritional intake emerging as a pivotal factor influencing adolescent health and productivity. Ensuring teenagers receive optimal nutrition and accurate information is essential for supporting their growth and development. Without preventive measures, nutritional issues in adolescence may persist into adulthood. The objective of this outreach initiative is to delineate the nutritional status of eighth-grade students at YPPK Santu Paulus Middle School. This undertaking involves anthropometric assessments and educational interventions aimed at enhancing awareness of nutritional status among adolescents. The findings revealed the participation of 91 students, and the measurements indicated that 39 individuals experienced malnutrition, 31 had a normal nutritional status, 12 were overweight, 7 exhibited level I obesity, and 2 demonstrated level II obesity.